'Four walls and a garden': Exploring the experiences of families affected by dementia during the COVID-19 pandemic. (April 2022) - Cousins, Emily; de Vries, Kay; Harrison Dening, Karen
Introduction: When the first national COVID-19 lockdown came into effect in the UK in March 2020, life changed significantly. Some services and social contacts for people with dementia and their families stopped, while others, for example, peer support, moved online. This research explored the experiences of families affected by dementia during the pandemic, specifically those living in the community. Aims: In partnership with a community dementia charity, this study sought to gain an understanding of the experiences of people with dementia and family carers during the COVID-19 pandemic and explore the impact and implications of lockdown on people with dementia and family carers. Methods: This was a qualitative study that used semi-structured interviews to collect data from people with dementia and family carers. Interviews were conducted online via video call, individually or within caring dyads. Initially, data were coded, analysed and themed inductively. Additionally, social disruption and social division theories were used to deductively identify patterns in the data to enhance understanding. Findings: Six distinct themes were identified from the inductive analysis: Routine: 'busy life before lockdown '; Isolation: ' four walls and a garden '; Living with restrictions: ' treading on eggshells' ; Discovering positives: 'you are in the same boat '; Easing lockdown: ' raring to go '; Heightened uncertainty: ' things have changed '. Illustrative examples of symptoms of social disruption and division were identified within the data: frustration, democratic disconnection, fragmentation, polarisation and escalation. Conclusion: Experiences of people with dementia and family carers during the pandemic were mixed, resulting in hopes and worries for the future. Social disruption and social division are relevant frameworks for analysing experiences of COVID-19.